Program for calculating the technological and structural characteristics of plate and packed distillation columns for separating two, multicomponent mixtures and isotopes; Journal of Physics: Conference Series; Vol. 2147 : Modern problems in Physics of separation in nuclear fuel cycle - Sukhar P. A. Pavel Andreevich (2022, 2022)
Title screen